Nano Biosensors for Prediction of Environmental Pollutants - Kumar, S. Vijay; Tejashwini, M. Amulya (Chronicle of Bioresource Management, 2024)
Nano biosensors are an advanced tool for environmental monitoring, integrating nanotechnology with biological recognition elements to achieve high sensitivity, specificity, and rapid pollutant detection. These sensors rely on nanomaterials such as gold nanoparticles, carbon nanotubes, and graphene to enhance signal transduction, while biological components like enzymes, antibodies, and nucleic acids provide selective detection of target pollutants. Recent developments have led to the creation of portable, miniaturized, and multiplexed sensors, enabling real-time, on-site monitoring of water, air, and soil quality. Despite their promise, significant challenges remain, particularly regarding sensitivity, stability, and potential interference from complex environmental matrices. High production costs and the lack of uniform regulatory guidelines also impede their widespread commercial adoption. Further improvements in nanomaterial design and sensor integration are required to address these limitations. Establishing robust regulatory frameworks and cost-effective production methods will be crucial in fully realizing the potential of nano biosensors for sustainable environmental monitoring and pollution control.